Human Rights - Freeman, Michael, 1936- (Key concepts (Polity Press), 2022)
Human Rights, now in its fourth edition, is an introductory text that is both innovative and challenging. Its unique interdisciplinary approach invites students to think imaginatively and rigorously about one of the most important and influential political concepts of our time. Tracing the history of the concept, the book shows that there are fundamental tensions between legal, philosophical and social-scientific approaches to human rights. This analysis throws light on some of the most controversial issues in the field: What are the causes of human-rights violations? Is the idea of universal human rights consistent with respect for cultural difference? Are we living in a 'post-human rights' world? Thoroughly revised and updated, the new edition engages with recent developments, including the Trump and Biden presidencies, colonial legacies, neoliberalism, conflict in Syria, Yemen and Myanmar, the Covid-19 pandemic, new technologies and the supposed crisis of liberal democracy.